Comparison and validation of sensors for 3D and 2D motion capture to measure 10-pin bowling specific kinematics - Lim, Matthew Jing Long (Nanyang Technological University, 2023)
Ten pin bowling is a competitive sport that requires athletes to score as many pins possible using a bowling ball. This project aims to provide a means for coaches and bowlers of Team Singapore to measure specific kinematic movements related to the sport. The bowling movements measured are the Anterior Trunk Flexion and the wrist acceleration and velocity of the bowler during the five-step movement, which will be quantified using data from Inertial Measurement Unit (IMU) sensors. Two IMU sensors will be used in this project, a proprietary sensor, Sensor A, as well as a commercially available sensor, Xsens Dot. The sensors are first compared against each to determine the sensor more viable for deployment in an actual bowling lane. In addition, the ultrawide-band (UWB) technology provided by Sensor A was also validated to determine the usability in an actual field setting. Upon the determination of a more suitable sensor, tests were conducted in a laboratory setting to mimic the actual movement on a bowling lane using the selected IMU sensor. The data was collected and compared against the Vicon motion capture camera system, which is regarded as the gold standard for video motion capture technology. Based on the data collected, it was validated that the ATF angle and wrist acceleration values recorded by the IMU sensor were relatively accurate compared to the data recorded by Vicon. The data recorded for the wrist velocity parameter showed a much larger discrepancy compared to Vicon data and is thus not an accurate indicator of an athlete's performance. Hence, the recommendation is to use the IMU sensor to measure the ATF angles and wrist acceleration values as a benchmark of the kinematic ability of the bowler.